Development of a personified face emotion recognition technique using fitness function - Muthukaruppan, Karthigayan; Mohd Rizon, Mohamed Juhari; Ramachandran, Nagarajan; Masanori, Sugisaka; Sazali, Yaacob; Mohd Rozailan, Mamat; Hazry, Desa (Springer Japan, 2009)
Link to publisher's homepage at http://www.springerlink.com